Formative Research for a Healthy Diet Intervention Among Inner-City Adolescents : The Importance of Family, School and Neighborhood Environment - Dodson, J. L.; Hsiao, Y. C.; Kasat-Shors, M.; Murray, L.; Nga, K. N.; Richards, A. K.; Gittelsohn, J. (2012)
Objectives: To understand influences on diet among low-income African-American adolescents in East Baltimore. Methods: Formative research was conducted for a food store-centered healthy diet intervention targeted to inner-city youth. Family, school and neighborhood influences on eating habits and health concepts were explored. Results: Family structure, economic resources and past experiences influence what food means to adolescents. Healthy food in school and local stores is limited. Terminology to categorize foods was identified, including the term home foods. Conclusions: Suggested adolescent nutritional interventions include promotion of home-based eating, improving availability of healthy foods in school and neighborhood stores, and targeted educational materials.